Optimasi Kecepatan Putar dalam Peningkatan Mutu Biji Kemiri pada Mesin Pemecah Cangkang Biji Kemiri (Aleurites moluccana willd.) - Sutejo, Agus; Fajri, Rahmatul; Sucahyo, lilis (Jurnal Agricultural Biosystem Engineering, 2023)
Postharvest handling of candlenut in the traditional way is less effective and efficient. A worker is only able to break as much as 9–10 kg of candlenut/day and this also causes high work fatigue, besides thas many kernels are broken and destroyed (percentage og intact round kernels is only 40–60 %) so the price of candlenut becomes cheaper. Therefore, a candlenut crushing machine is needed with an optimum rorational speed that able to provide optimal and consistent energy to candlenuts crushing result. The candlenut material was dried at at 90 ˚C for 3 and 4 hours, then put it in ice water at 5 ˚C for 15 minutes. It was drained for 20 minutes and a drop test was carried out to find the optimum energy and rotational speed in cracking the candlenut. The result of rotaional speed are set up on the candlenut shell breking machine. Optimum solving result obtained of 490,5 Joules. Equivalent to candlenut dropped from a height of 5 meters with a rotating speed of 337,88 rpm. Keywords:  Candlenut, Post Harvest, Rotational Speed